Functional MRI Readouts From BOLD and Diffusion Measurements Differentially Respond to Optogenetic Activation and Tissue Heating - Albers, Franziska; Wachsmuth, Lydia; Schache, Daniel; Lambers, Henriette; Faber, Cornelius (Frontiers in Neuroscience, 2019)
Functional blood-oxygenation-level-dependent (BOLD) MRI provides a brain-wide readout that depends on the hemodynamic response to neuronal activity. Diffusion fMRI has been proposed as an alternative to BOLD fMRI and has been postulated to directly rely on neuronal activity. These complementary functional readouts are versatile tools to be combined with optogenetic stimulation to investigate networks of the brain. The cell-specificity and temporal precision of optogenetic manipulations promises to enable further investigation of the origin of fMRI signals. The signal characteristics of the diffusion fMRI readout vice versa may better resolve network effects of optogenetic stimulation. However, the light application needed for optogenetic stimulation is accompanied by heat deposition within the tissue. As both diffusion and BOLD are sensitive to temperature changes, light application can lead to apparent activations confounding the interpretation of fMRI data. The degree of tissue heating, the appearance of apparent activation in different fMRI sequences and the origin of these phenomena are not well understood. Here, we disentangled apparent activations in BOLD and diffusion measurements in rats from physiological activation upon sensory or optogenetic stimulation. Both, BOLD and diffusion fMRI revealed similar signal shapes upon sensory stimulation that differed clearly from those upon heating. Apparent activations induced by high-intensity light application were dominated by T2*-effects and resulted in mainly negative signal changes. We estimated that even low-intensity light application used for optogenetic stimulation reduces the BOLD response close to the fiber by up to 0.4 %. The diffusion fMRI signal contained T2, T2* and diffusion components. The apparent diffusion coefficient, which reflects the isolated diffusion component, showed negative changes upon both optogenetic and electric forepaw stimulation. In contrast, positive changes were detected upon high-intensity light application and thus ruled out heating as a major contributor to the diffusion fMRI signal.